Studi Resepsi Pada Konten Instagram @Hopehelpsnet Dalam Upaya Menciptakan Ruang Aman Dari Kekerasan Seksual di Kampus - Septariani, Aisyah Dwina; Putri, Citra Eka; Sadono, Wahyu Sri (Prisani Cendekia Institute, 2025)
Technological advance have so much adventage of mankind that can be used in many things. Social media utilization to build mass awareness as Hopehelps Network do in the way they campaign safe space from sexual violence in university with victim and gender perspective. Hopehelps Network taking advantage from Instagram as a tools to deliver urgency about the safe space from sexual violence at university. This thesis explore further about how audience interpreted the message from the @Hopehelpsnet’s Instagram content, using reception theory proposed by Stuart Hall encoding/decoding. Reception theory put audience in three position, which is dominant-hegemonic position, negotiation position, oppositional position.